EFFECTIVENESS OF BREAST CARE ON THE SMOOTH DELIVERY OF BREAST MILK - Agus Sulistyowati (Nurse and Health: Jurnal Keperawatan, 2018)
The breastfeeding program for babies is very encouraged by the government on the grounds that there are many benefits of breastfeeding that can be given to babies. One of the supporting factors for the success of the program is to prepare the breast so that it can produce abundant milk and contains lots of nutrients. Preparation of pregnant women to provide quality breastfeeding is by treating the breast during pregnancy in the final trimester of pregnancy. Warm massage and compresses on the breast have several effects, including improving blood flow and making the nipple more elastic and not easily scratched when breastfeeding later.Key words: Pregnant women, breast care, breastfeeding.